Effect Employing the PDEODE Six-Dimensional Strategy in Developing Mathematical Connection Skills and Mathematical Knowledge Management among Tenth-Grade Science Students (Journal of the College of Basic Education, 2026)
This study aims to investigate the effect of employing the Six-Dimensional Strategy (PDEODE) on developing mathematical connectivity skills and mathematical knowledge management skills among tenth-grade scientific stream female students. To verify the research objectives, the researcher adopted a quasi-experimental design with partial control. The experiment was conducted on a sample of (61) female students from the tenth grade at Zayan Preparatory School, under the Independent Zakho Education Directorate, during the academic year (2023–2024). The sample was selected purposively from the research population and randomly distributed into two equivalent groups: an experimental group consisting of (31) students who studied the subject according to the PDEODE strategy, and a control group consisting of (30) students who studied the same subject using the conventional method.To achieve the research objectives, the researcher developed two instruments. The first was a Mathematical Connectivity Test comprising (30) multiple-choice items distributed across three skills: (1) knowing and applying relationships among mathematical ideas, (2) understanding the interconnection between mathematical ideas and how they are constructed, and (3) connecting mathematics to real life and other sciences. The second instrument was a Mathematical Knowledge Management Scale, consisting in its final form of (20) items distributed across five skills knowledge construction, knowledge organization, knowledge representation, knowledge application, and knowledge evaluation with (4) items per skill, responded to on a three-point Likert scale (Agree, Neutral, Disagree) , Following verification of the psychometric properties of both instruments, the researcher implemented the experiment after providing the mathematics teacher with all lesson plans for both the experimental and control conditions at the beginning of the second semester. Upon completion of the experiment, the Mathematical Connectivity Test and the Mathematical Knowledge Management Scale were administered on two consecutive days, on 17–18 April 2024. Data were collected and statistically analyzed using the SPSS software package, yielding the following findings:Statistically significant differences at the (α = 0.05) significance level were found between the mean scores of the two research groups in favor of the experimental group in the development of mathematical connectivity skills.Statistically significant differences at the (α = 0.05) significance level were found between the mean scores of the two research groups in favor of the experimental group in the development of mathematical knowledge management skills.Statistically significant differences at the (α = 0.05) significance level were found between the pre-test and post-test mean scores of the experimental group — which studied according to the PDEODE strategy — on both mathematical connectivity and mathematical knowledge management skills, in favor of the post-test. In light of these findings, the researcher put forward several recommendations, including the integration of the PDEODE strategy within mathematics curricula in relation to mathematical connectivity skills and knowledge management. A number of suggestions were also presented for directing future research in this area.